Assessment of S100A8/A9 and resistin as predictive biomarkers for mortality in critically ill patients with sepsis - Jing Chen; Jing Chen; Jing Chen; Jing Chen; Jing Chen; Jing Chen; Zhengquan Liu; Zhengquan Liu; Zhengquan Liu; Zhengquan Liu; Zhengquan Liu; Zhengquan Liu; et al. (Frontiers in Cellular and Infection Microbiology)
IntroductionSepsis is associated with high mortality. Early intervention is crucial to reducing sepsis-related mortality. This study aims to assess the clinical potential of S100A8/A9 and resistin as novel biomarkers for predicting mortality risk in sepsis patients.MethodSerum samples were collected and analyzed from 141 adult sepsis patients (discovery cohort), 43 non-sepsis intensive care units (ICU) patients, 15 healthy volunteers, and 55 sepsis patients along with 17 non-sepsis ICU patients (validation cohort). The 28-day mortality and sequential organ failure assessment (SOFA) scores of the participants were compared. Additionally, the predictive ability of S100A8/A9 and resistin for sepsis mortality was evaluated using the area under the receiver operating characteristic curve at ICU admission.ResultsThe concentrations of S100A8/A9 and resistin in sepsis patients were noticeably increased relative to non-sepsis patients and healthy controls. Serum S100A8/A9 concentrations in surviving sepsis patients were significantly higher than in non-surviving patients. On the day of admission, serum resistin concentrations in Gram-negative (G-) sepsis patients were considerably elevated relative to Gram-positive (G+) infected sepsis patients. Among sepsis patients admitted to the ICU, the AUC for S100A8/A9 in predicting 28-day mortality was 0.617 (P = 0.032; 95% confidence bounds 0.513–0.721), and for SOFA was 0.750 (P < 0.0001; 95% confidence bounds 0.660–0.840). Sepsis patients with high serum S100A8/A9 concentrations (≥ 377.53 ng/mL) had a higher survival rate relative to those with low concentrations (<377.53 ng/mL). In the validation cohort, the AUC for S100A8/A9 and 28-day mortality was 0.708 (P = 0.032; 95% confidence bounds 0.563–0.854), and for SOFA was 0.698 (P = 0.025; 95% confidence bounds 0.550–0.845). Additionally, sepsis patients with high serum S100A8/A9 concentrations (≥ 377.53 ng/mL) also had a higher survival rate relative to those with lower concentrations (< 377.53 ng/mL). Furthermore, serum resistin levels in patients with a normal phenotype and mixed phenotype with hyperinflammation were predictive of mortality, with an AUC of 0.810 (P = 0.034; 95% confidence bounds 0.605–1.00) and 0.708 (P = 0.015; 95% confidence bounds 0.571–0.846). In patients with a normal sepsis phenotype, those with high serum resistin levels (≥ 63.695 ng/mL) had a lower survival rate compared to those with low resistin levels (< 63.695 ng/mL). In contrast, in patients with a mixed phenotype with hyperinflammation, those with high serum resistin levels (≥ 107.64 ng/mL) had a higher survival rate compared to those with lower resistin levels (< 107.64 ng/mL).DiscussionSepsis, the leading cause of death in intensive care unit patients. Identifying reliable biomarkers is essential for improving both the diagnosis and treatment of sepsis. We found that serum S100A8/A9 concentration at ICU admission is a significant predictor of 28-day mortality risk in sepsis patients. Additionally, resistin levels at ICU admission play an important role in predicting 28-day mortality risk in patients with both normal and mixed phenotypes with hyperinflammation. These findings suggest that S100A8/A9 and resistin could serve as effective biomarkers. Moreover, these findings could guide early clinical decisions in the treatment of sepsis patients.